Free trade (agreement fta) between Colombia and United States, and the benefits for Colombian exporters (2013)
Globalization and economic liberalization in Colombia start from former President Virgilio Barco and was materialized with more force in the government of former President Cesar Gaviria Trujillo, an episode that gave way to the Neoliberal Political movement, leaving aside the protectionist model adopted by Colombia until 1991, where companies produce only to meet demand nationwide, without any competition that would improve the quality of products and competition from them.